Peer-led counselling with problem discussion therapy for adolescents living with HIV in Zimbabwe: A cluster-randomised trial. - Victoria Simms; Helen A Weiss; Silindweyinkosi Chinoda; Abigail Mutsinze; Sarah Bernays; Ruth Verhey; Carol Wogrin; Tsitsi Apollo; Owen Mugurungi; Dorcas Sithole; Dixon Chibanda; Nicola Willis (PLoS Medicine)
Background Adolescents living with HIV have poor virological suppression and high prevalence of common mental disorders (CMDs). In Zimbabwe, the Zvandiri adolescent peer support programme is effective at improving virological suppression. We assessed the effect of training Zvandiri peer counsellors known as Community Adolescent Treatment Supporters (CATS) in problem-solving therapy (PST) on virological suppression and mental health outcomes. Methods and findings Sixty clinics were randomised 1:1 to either normal Zvandiri peer counselling or a peer counsellor trained in PST. In January to March 2019, 842 adolescents aged 10 to 19 years and living with HIV who screened positive for CMDs were enrolled (375 (44.5%) male and 418 (49.6%) orphaned of at least one parent). The primary outcome was virological nonsuppression (viral load ≥1,000 copies/mL). Secondary outcomes were symptoms of CMDs measured with the Shona Symptom Questionnaire (SSQ ≥8) and depression measured with the Patient Health Questionnaire (PHQ-9 ≥10) and health utility score using the EQ-5D. The adjusted odds ratios (AORs) and 95% confidence intervals (CIs) were estimated using logistic regression adjusting for clinic-level clustering. Case reviews and focus group discussions were used to determine feasibility of intervention delivery. At baseline, 35.1% of participants had virological nonsuppression and 70.3% had SSQ≥8. After 48 weeks, follow-up was 89.5% for viral load data and 90.9% for other outcomes. Virological nonsuppression decreased in both arms, but there was no evidence of an intervention effect (prevalence of nonsuppression 14.7% in the Zvandiri-PST arm versus 11.9% in the Zvandiri arm; AOR = 1.29; 95% CI 0.68, 2.48; p = 0.44). There was strong evidence of an apparent effect on common mental health outcomes (SSQ ≥8: 2.4% versus 10.3% [AOR = 0.19; 95% CI 0.08, 0.46; p < 0.001]; PHQ-9 ≥10: 2.9% versus 8.8% [AOR = 0.32; 95% CI 0.14, 0.78; p = 0.01]). Prevalence of EQ-5D index score <1 was 27.6% versus 38.9% (AOR = 0.56; 95% CI 0.31, 1.03; p = 0.06). Qualitative analyses found that CATS-observed participants had limited autonomy or ability to solve problems. In response, the CATS adapted the intervention to focus on empathic problem discussion to fit adolescents' age, capacity, and circumstances, which was beneficial. Limitations include that cost data were not available and that the mental health tools were validated in adult populations, not adolescents. Conclusions PST training for CATS did not add to the benefit of peer support in reducing virological nonsuppression but led to improved symptoms of CMD and depression compared to standard Zvandiri care among adolescents living with HIV in Zimbabwe. Active involvement of caregivers and strengthened referral structures could increase feasibility and effectiveness. Trial registration Pan African Clinical Trials Registry PACTR201810756862405.